Long-term outcomes of “open iridectomy” for secondary anterior chamber epithelial iris cysts - Jie Lan (Nature Portfolio, 2021)
Abstract Epithelial cysts run a high risk of recurrence and conversion to sheet-like ingrowth after surgical intervention. In this retrospective study, we introduced a modified iridectomy for treatment of secondary epithelial iris cysts (EICs) in the anterior chamber. Twenty-nine patients (29 eyes) aged 2–61 years received “open iridectomy” for EICs between April 1995 and July 2019. After viscodissection, most of the cyst wall was cut using a 20-gauge aspiration cutter via a 2.5-mm clear corneal incision. The residue closely adhering to the iris stroma was remained to avoid photophobia and diplopia. At 3 months, best corrected visual acuity was ≥ 20/100 in 55.5% (15/27, except two pediatric patients with poor cooperation) of patients. Among the eight patients suffering partial corneal edema preoperatively, six patients received surgery treatment at 3–6.5 months, and the cornea in the other two patients became transparent after medication. In a mean follow-up of 47.4 months, recurrence occurred in 3 patients at 7, 37, and 118 months, respectively. The percentage of treatment success was 96%, 87%, and 65% at 1, 5, and 10 years, respectively. “Open iridectomy” was effective for EICs, with a minimal invasion, less damage to the corneal endothelium, and a low recurrence rate.